Partnering with HMS : a guide for app developers - Wang, Xihai, 1980-; Wang, Yue, 1977-; Wu, Hailiang, 1983- (Boca Raton : CRC Press, 2022)
"This is the first book to introduce the Huawei Mobile Services (HMS) ecosystem. It gives developers a basic understanding of the ecosystem and how to leverage kit and tool capabilities to make their apps better"--
OCLC-licensed vendor bibliographic record.
Keywords: Hua wei ji shu you xian gong si; Mobile computing; Application software -- Development; COMPUTERS / General; COMPUTERS / Computer Science; COMPUTERS / Operating Systems / General